Responding to sustained poor outcomes in the management of non-communicable diseases (NCDs): an "incident control" approach is needed to improve and protect population health - Julia Knight; Matthew Day; John Mair-Jenkins; Chris Bentley; Ben Anderson; Fu-Meng Khaw (BMC, 2019)
Abstract In 2017 Public Health England were asked to assist with investigating why 1-year cancer survival rates appeared lower than expected in a local area. We identified 50 premature deaths that surveillance data suggested we would not expect. These deaths highlighted a gap in recognising and responding to this kind of systematic non communicable disease (NCD) outcome variation. We hypothesise that the lack of a universally agreed systematic response to variations is not only counter-intuitive, but wholly unacceptable where non-communicable diseases (NCDs) rather than infectious diseases have become the leading causes of illness and death worldwide. In the United Kingdom (UK) alone over 89% of mortality in 2014 was attributable to NCDs. We argue that a new approach is urgently needed to turn the curve on NCD outcome variation to protect and improve the public's health. We set out a definition of an NCD "incident" and propose a phased approach that could be used to respond to local variation in NCD outcomes. Establishing parity of response for local variations in NCD outcomes and CD control is critically important. Although evidence shows that prevention and early intervention will make the biggest difference to NCD incidence, collective local whole health economy response, exploiting the wealth of surveillance data in real time, needs to be at the heart of responding to variations in NCD outcomes at a population level. We argue that local and national public health agencies should mandate a standardised 'incident' response to significant changes in outcomes from NCD to mitigate and reduce the loss of quality life.